"Is It the Message or the Messenger?": Conspiracy Endorsement and Media Sources. (December 2021) - Mancosu, Moreno; Vegetti, Federico
Public opinion literature on conspiracy theories mainly focuses on individual and contextual factors predicting people's beliefs in conspiratorial news. However, little research to date has considered the role of the source of the news, and its interaction with the news content, in explaining people's receptivity to those narratives. By employing a survey experiment on a sample of U.S. citizens, we test whether the conspiratorial/debunking content of a news and the type of media outlet publishing it (mainstream/independent) affect people's perceptions of the news plausibility. Respondents are asked to evaluate the plausibility of a news headline supporting or debunking a well-known conspiracy theory (chemtrails), attributed to a mainstream media outlet or an independent blog. Results show that (1) conspiracy believers are more likely to believe in the conspiratorial account than in the debunking account and (2) the effect is stronger when the news comes from an independent source rather than a mainstream one.